2021
DOI: 10.1177/00469580211060291
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Healthcare Workers Caring for COVID-19 Patients in Indonesia: A Qualitative Study

Abstract: COVID-19 pandemic raises various challenges faced by health workers in hospitals. This study explored strategies for overcoming challenges in caring for COVID-19 patients at hospitals in Indonesia based on healthcare workers’ experience. In-depth interviews were employed with 28 healthcare workers (physicians and nurses) who were purposively sampled. Data were collected via phone and analysed using the Colaizzi method. Five following challenges were found: difficulties in working with personal protective equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Limitations in infrastructural resources resulting in few hand washing stations and patient control or quarantine areas in emergency or other healthcare environments promoted increased risk of COVID-19 transmission by preventing sufficient adherence to prevention strategies [ 9 , 11 , 12 , 13 , 14 ]. Several studies have also reported adherence barriers arising from inadequate in-service training on COVID-19 infection prevention and control measures, the proper use of PPEs, and pitfalls and challenges in extended use of uncomfortable PPEs in patient care settings [ 9 , 11 , 12 , 14 , 16 , 17 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in infrastructural resources resulting in few hand washing stations and patient control or quarantine areas in emergency or other healthcare environments promoted increased risk of COVID-19 transmission by preventing sufficient adherence to prevention strategies [ 9 , 11 , 12 , 13 , 14 ]. Several studies have also reported adherence barriers arising from inadequate in-service training on COVID-19 infection prevention and control measures, the proper use of PPEs, and pitfalls and challenges in extended use of uncomfortable PPEs in patient care settings [ 9 , 11 , 12 , 14 , 16 , 17 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 20 More notably, recent findings suggest that COVID-19 has had an important influence on the psychological well-being and mental health of healthcare professionals. 21 - 23 Those healthcare professionals who are engaged with social media during COVID-19 are more exposed to psychological problems. 4 During the pandemic, there was a noticeable increase in social media engagement among healthcare professionals.…”
Section: Coi On Social Media and Healthcare Professional’s Health And...mentioning
confidence: 99%
“…The disease resulting from nearly 500 million confirmed SARS-CoV-2 infections (COVID- 19) had caused approximately 6 million deaths globally [1]. Healthcare workers (HCWs) serving these patients are at high risk of becoming infected [2,3].…”
Section: Introductionmentioning
confidence: 99%